An experimental study on improving the performance of a double slope solar still - Alawee, Wissam Hameed; Dhahad, Hayder Abed; Mohammed Ali, Thamer Ahmed (2015)
Distilled water productivity of the conventional solar stilled is still very limited. This has called for more research to improve efficiency and increase productivity. The present work is an experimental study to improve the productivity of the conventional solar still. This done by three methods which work at the same time. They are: a) modifying conventional design to the proposed design to ensure increase in the condensation surface, b) by coupling of collector/storage solar water heater to solar still. It will heat the water before it is sent to the solar still, and c) using gravel as a suitable storage material to store heat energy to be used when sunlight is not available. For this purpose , two solar stills were made, one conventional design and another made according to the proposed design. The two solar stills were tested during the period from February to July 2014 under varying weather conditions of Baghdad, Iraq (latitude of 33.33 and longitude of 44.43). The results show that integrating the solar still with Internal reflective panels increases the distillate water by 18.5%. And using collector/storage solar water heater and gravel material improves the productivity by 48%.